Cold Dialysis Solution for Hemodialysis Patients With Fatigue: a Cross-over Study (Iranian Journal of Kidney Diseases, 2016)
Introduction. The purpose of this study was to explore the effect of cold dialysis on fatigue in hemodialysis patients. Materials and Methods. In a double-blinded cross-over clinical trial, 46 participants were recruited from a hemodialysis unit in Iran. The participants were allocated into 2 groups through simple random sampling method. Each group received 3 sessions of hemodialysis with a dialysis solution temperature of either 37°C 3 or 35.5°C during the first week and then with for another week with the other temperature.  The self-report Piper Fatigue Scale questionnaire was filled out by the participants. Results. The Piper Fatigue Scale scores in the cold dialysis groups were significantly lower than those in the conventional dialysis solution temperature (P < .001). Reducing the temperature of hemodialysis solution brought a 31.3% reduction in the fatigue score. Conclusions. Cold dialysis can be used for all hemodialysis patients as a routine intervention, and in particular, it is recommended dialysis patients who have severe fatigue as a convenient and inexpensive therapeutic option.